Development of Online Science Teaching Instrument Based on Scientific Approach Using PhET Simulation to Improve Learning Outcomes at Elementary School - Taufik Adi Sarwoto; Budi Jatmiko; Elok Sudibyo (IJORER : International Journal of Recent Educational Research, 2020)
The research aims to develop online science teaching instruments based on a scientific approach using a proper PhET simulation to improve learning outcomes for elementary school students. The developed equipment is the lesson plan, students’ activity sheet, learning materials, and assessment sheet of learning outcomes. The research plan is designed in One Group Pre-Test- Post-Test Design. The population in this study is all students of the fifth grade of State Elementary School Jagir I academic year 2019/2020. The results showed that there is a significant improvement in the results of online science studying through a scientific approach with the PhET simulation media. N-Gain value of class A is of 0.76 and class B is 0.70 with high criteria. The hypothesized test results showed no significant difference between class A and class B, student learning outcomes in the psychomotor area values class A in 80 when the average value of class B is 77.08, the learning results in affective domain values in class A is 80.00 in average and in class B is 80.31 with the 100% passing rate of the affective domain.